Apollo's gold - Moses, Antoinette (Cambridge English readers. Level 2, 1999)
Liz studies and teaches archaeology in Athens. While on vacation on Sifnos a mysterious yacht arrives, one of the local men dies, and Liz becomes involved with some very dangerous people.